Estimation Of Heritability Value on Body Weight, Egg Weight, and Egg Index Arabic Chicken in BPBTNR Chicken Satker Maron, Temanggung - Dwi Winta Nur Insani; Pradipta Bayuaji Pramono; Mikael Sihite; Rahayu Kusumaningrum (Universitas Tidar, 2023)
Arabic chicken is one of the local chickens that have superior productivity. Government efforts to continue increasing livestock productivity and genetic quality can be carried out through breeding programs based on genetic parameters, including heritability. Research on estimating heritability in Arabic chickens has never been reported at the BPBTNR Maron Working Unit. This research aims to determine the heritability of Arabic chicken's body weight, egg weight, and egg index. The sample used was 50 healthy Arabian chickens aged ten months. The eggs used came from matings between Arab hens and Arab hens with a ratio of 1:5, namely ten males and 50 females. Chickens and eggs were measured using digital scales and calipers. The statistical method used is ANOVA (Analysis of Variance) analysis followed by descriptive analysis. Heritability values were calculated using the half-sibling correlation method (paternal half sibling correlation). The results showed that the average body weight, egg weight and egg index in the Maron Chicken Satker BPBTNR, Temanggung were 1,270 ± 0.21 g, 45.37 ± 3.68 g and 76.10 ± 3.27, respectively. Meanwhile, the heritability value of the body weight of Arabic chickens was classified as moderate (0.145 ± 0.344), egg weight (0.355 ± 0.361) and egg index (0.464 ± 0.371) was classified as high. Keywords: arabic chicken, heritability, average value